Patch testing in allergic contact dermatitis over the lower extremities - Bommireddy Vinay Kumar; P Kombettu Ashwini; Garehatty Rudrappa Kanthraj; B Betkerur Jayadev (Wolters Kluwer Medknow Publications, 2019)
Background: There is an increased incidence of allergic contact dermatitis (ACD) over the lower extremities due to over-the-counter topical preparations, occupational risk, and usage of several chemicals in the manufacture of designer footwear. Aims and Objectives: The aim of the study was to identify the common allergens and polysensitization pattern involved in ACD over the lower extremities. Materials and Methods: It is a cross-sectional study, wherein a total of 80 patients were recruited over a period of 18 months. Demographic and clinical characteristics were noted. Patch test was done with the Indian standard series. Interpretation of patch test readings was read according to the International Contact Dermatitis Research Group criteria at 48 and 96 h. Results: There were 45 males and 35 females (M:F= 1.3:1). Mean age was 41.65 years. Most of the patients belonged to 21-40 years age group. Farmers, homemakers, and students were commonly affected. Most common presentation was itching, hyperpigmentation, and scaly plaques over the feet. Patch test was performed in 75% of the patients. One or more positive results were observed in 57% of the patients. Common allergens noted were potassium dichromate (35%), followed by nickel sulfate (23.5%), mercapto mix, and mercaptobenzothiazole. Potassium dichromate and nickel were the common allergens reported in males and females, respectively. Neomycin was the common medication responsible for dermatitis medicamentosa. Polysensitization was seen with mercapto mix, mercaptobenzothiazole, potassium dichromate, and fragrance mix. Conclusion: Potassium dichromate and nickel were the common allergens responsible for ACD over the lower extremities. Polysensitization was seen commonly with mercapto mix, mercaptobenzothiazole, and fragrance mix. Recommendation: Screening for usage of topical preparations and late patch test readings (96 h or more) is recommended.